2017
DOI: 10.1016/j.fuel.2017.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised classification of petroleum Certified Reference Materials and other fuels by chemometric analysis of gas chromatography-mass spectrometry data

Abstract: As feedstocks transition from conventional oil to unconventional petroleum sources and biomass, it will be necessary to determine whether a particular fuel or fuel blend is suitable for use in engines. Certifying a fuel as safe for use is time-consuming and expensive and must be performed for each new fuel. In principle, suitability of a fuel should be completely determined by its chemical composition. This composition can be probed through use of detailed analytical techniques such as gas chromatography-mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…In fact, modern analytical platforms of separation followed by different detection techniques, e.g. tandem gas chromatography-mass spectrometry (GC-MS) [5][6][7], liquid chromatography-mass spectrometry or diode-arrays spectrophotometer (LC-MS [8,9], LC diode-array spectroscopy (LC-DAD) [10,11]), and capillary electrophoresis (CE) with DAD [12], have been scarcely applied. Conversely, fluorescence spectroscopy is the direct detection technique that has been mostly exploited in order to solve classification issues.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, modern analytical platforms of separation followed by different detection techniques, e.g. tandem gas chromatography-mass spectrometry (GC-MS) [5][6][7], liquid chromatography-mass spectrometry or diode-arrays spectrophotometer (LC-MS [8,9], LC diode-array spectroscopy (LC-DAD) [10,11]), and capillary electrophoresis (CE) with DAD [12], have been scarcely applied. Conversely, fluorescence spectroscopy is the direct detection technique that has been mostly exploited in order to solve classification issues.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…processes, storage, harvest or variety). Other relevant works have been orientated to more specific research, such as the forensic analysis of textile fibers [40,41], the characterization of organic constituents of soils [42], discrimination of geographical origin and detection of adulteration of burdook and kudzu roots [43,44], and for the identification of biodiesel and petroleum oils with environmental purposes [7,45,46]. Several recent reviews have been published about this ever increasing research field where relevant applications can be found [47][48][49][50][51][52][53].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…For biodiesel-diesel blended fuels, a long, very polar column is traditionally used to separate the many diesel components as well as to isolate the long chain fatty acid methyl esters (FAMEs) present in biodiesels [2][3][4]. The diesel components elute at low to mid-range temperatures and are often difficult to completely isolate, leading to unresolved baseline humps [5,6]. The alkanes have large, easily recognizable peaks with various aromatic components present in diesel and are interspersed throughout the chromatogram.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive two-dimensional gas chromatography (GC×GC) coupled to time-of-flight mass spectrometry (TOFMS) has become an established technique for the analysis of complex samples [1][2][3]. The increased peak capacity and sensitivity obtained through non-targeted GC×GC-TOFMS analysis result in complex data sets, which are time-consuming to analyze [4,5]. As such, multiple data reduction strategies have been implemented for the analysis of GC×GC-TOFMS data [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%